Analyst ratings for firms filing for and reorganizing under Chapter 11. Issue 3 (14th August 2017) - Precourt, Elena; Oppenheimer, Henry
Abstract : Purpose: The purpose of this paper is to examine analyst followings of firms starting from one year prior to their filing for Chapter 11 and as the firms progress through bankruptcy proceedings with a focus on firms receiving "Hold" or better recommendations. The authors attempt to answer questions such as what the common characteristics of the firms receiving stronger than expected recommendations one year prior to filing for bankruptcy reorganization or while in bankruptcy are, and how the market reacts to the issuance of stronger ratings for those firms. Design/methodology/approach: The authors design various regressions and apply them to a total of 2, 754 sell-side analyst recommendations and 325 firms that are either approaching bankruptcy filing or in the process of reorganizing. In each analysis, the authors control for several firm and performance characteristics. Findings: The authors find that the probability of securing stronger ratings is higher for small firms and for those followed by a greater number of analysts than for large firms and firms followed by fewer analysts. The market becomes more skeptical of optimistic evaluations closer to the date of bankruptcy filing (perhaps reflecting some anticipation) and reacts more positively to rating upgrades issued during bankruptcy protection than to the upgrades issued before the bankruptcy filing. Research limitations/implications: The conclusions are based on the analysis of analyst recommendations issued shortly before Chapter 11 filings and during bankruptcy proceedings. The conclusions could be strengthened by further analysis of firms' post-bankruptcy recovery and performance and examination of analyst recommendations issued for the firms after they emerge from Chapter 11.. Practical implications: Analyst security ratings that are more positive than expected are perhaps the result of superior expertise and access to private information. During bankruptcy proceedings, when information disclosure is limited, investors could greatly benefit from reports issued by security analysts. Originality/value: This study contributes to the literature in a number of ways. First, the authors contribute to the literature on the analyst ratings of firms in distress by considering the period between bankruptcy filing and emergence, while the existing literature provides analysis of pre-bankruptcy recommendations and forecasts. Second, the authors focus on better than expected ratings rather than all types of ratings as the firms approach bankruptcy filings and proceed through reorganization. Finally, they evaluate how investors react to stronger than expected analyst ratings.